THE GENUS SIGANUS IN THE COLLECTION OF THE NATIONAL INSTITUTE OF OCEANOLOGY (SIGANIDAE) - Burhanuddin, -; Martosewojo, Sularto; Hutomo, Malikusworo; Djamali, Asikin (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1975)
Ten species of the genus Siganus namely Siganus vulpinus, S. corallinus, S. spinus, S. oramin, S. javus, S. virgatus, S. puellus, S. chrysospilos, S. vermiculatus, and S. guttatus are available in the collection of the Lembaga Oseanologi Nasional (LON = National Institute of Oceanology). The description of each of these species is presented.